BASIS DATA APACHE CASSANDRA SEBAGAI MEDIA PENYIMPANAN DATA SENSOR DAN BACKEND INTERNET OF THINGS (IOT) - Rizki Ariyani (Jurnal Ilmiah Teknik, 2022)
Millions of data at every meeting are questioned through social media, application websites, mobile applications, and internet usage that uses objects around us to be able to interact with each other known as the Internet of Things (IoT). IoT requires a database with very high performance and a high level of availability. NoSQL is one database that can store diverse data. Currently there are many NoSQL databases with different implementation and storage characteristics. This brings challenges in the selection of NoSQL databases used as IoT data storage media. In several studies that have been carried out by several researchers who use IoT data storage media using the Apache Cassandra NoSQL Database. The results of literature studies and literature reviews show that Cassandra is the best apache that can be used as a data storage sensor, and backend Internet of Things (IoT).